1997
DOI: 10.1084/jem.186.9.1523
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Consensus Sequence Binding Protein–deficient Mice Display Impaired Resistance to Intracellular Infection Due to a Primary Defect in Interleukin 12 p40 Induction

Abstract: Mice lacking the transcription factor interferon consensus sequence binding protein (ICSBP), a member of the interferon regulatory factor family of transcription proteins, were infected with the intracellular protozoan, Toxoplasma gondii. ICSBP-deficient mice exhibited unchecked parasite replication in vivo and rapidly succumbed within 14 d after inoculation with an avirulent Toxoplasma strain. In contrast, few intracellular parasites were observed in wild-type littermates and these animals survived for at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
151
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 191 publications
(157 citation statements)
references
References 54 publications
6
151
0
Order By: Relevance
“…IL-12 drives type I immune responses, primarily by virtue of its ability to induce the production of IFN-␥ from T and NK cells. A number of studies have shown that animals deficient in IL-12 are more susceptible to infections by intracellular organisms (1,2), and conversely that the addition of exogenous IL-12 can promote protective immune responses to these organisms (3,4). Despite its conspicuous role in driving cellular immune responses, the overproduction of IL-12 can be detrimental to the host.…”
Section: Suppression Of Il-12 Transcription In Macrophages Followingmentioning
confidence: 99%
“…IL-12 drives type I immune responses, primarily by virtue of its ability to induce the production of IFN-␥ from T and NK cells. A number of studies have shown that animals deficient in IL-12 are more susceptible to infections by intracellular organisms (1,2), and conversely that the addition of exogenous IL-12 can promote protective immune responses to these organisms (3,4). Despite its conspicuous role in driving cellular immune responses, the overproduction of IL-12 can be detrimental to the host.…”
Section: Suppression Of Il-12 Transcription In Macrophages Followingmentioning
confidence: 99%
“…Samples were purified by phenol-chloroform and resolved in 6% PAGE. Details of RNase protection assays were described (24).…”
Section: Rnase Protection Assaymentioning
confidence: 99%
“…Further, ICSBP Ϫ/Ϫ mice express a very low level of constitutive IL-12 p40 transcripts and are unable to induce the transcripts in response to infections (23,24). Accordingly, ICSBP Ϫ/Ϫ mice are highly susceptible to infection by Listeria monocytogenes, Toxoplasma gondii, Leishmania major, and lymphocytic choriomeningitis virus and vaccinia viruses (23)(24)(25)(26). The study performed with the Toxoplasma model attributed this susceptibility to a specific defect in macrophages to induce IL-12 p40 mRNA (24).…”
mentioning
confidence: 99%
See 2 more Smart Citations